Diamond Schottky barrier diodes with floating metal rings for high breakdown voltage. (July 2019) - Wang, Juan; Zhao, Dan; Wang, Wei; Zhang, Xiaofan; Wang, Yanfeng; Chang, Xiaohui; Liu, Zhangcheng; Fu, Jiao; Wang, Kaiyue; Wang, Hong-Xing
Abstract: Investigation of influence of floating metal rings (FMRs) edge termination technique on the breakdown voltages of diamond Schottky barrier diodes (SBDs) has been carried out. Unintentionally doped P - drift layer was grown on HPHT boron doped diamond substrate by microwave plasma CVD system and treated by ultraviolet ozone. Then, Ti/Ni/Au electrode was deposited on the back side of the substrate to form ohmic contact. Zr/Ni/Au Schottky electrodes with different FMRs parameters, such as ring spacing (RS ), ring width (RW ) and ring number (RN ), were deposited on the P - layer. The I–V measurement results show that breakdown voltages increase firstly and then decease with increasing of RS . The increases of RW and RN are beneficial to improve breakdown voltages. Moreover, FMRs structure can effectively improve breakdown voltages without deteriorating forward current density and rectification ratio of diamond SBDs.